Optimizing flow cytometry analysis for determining ploidy level and genome size of colchicine-induced polyploids of Neolamarckia cadamba - Ho, Wei Seng; Eng, Wee Hiang; Ling, Kwong Hung (Open Science Publishers LLP, 2024)
Flow cytometry (FCM) analysis plays a crucial role in polyploidization studies. It allows for the rapid identification of induced polyploids or mixoploids and plantlets with unchanged ploidy levels compared to the conventional method of chromosome counting. Therefore, the present study aims to optimize and develop an efficient FCM analysis procedure to determine the ploidy level and DNA content of Neolamarckia cadamba. This involved investigating various types of leaf tissues of N. cadamba and lysis buffers to identify the best tissue-buffer combination for FCM analysis. The histograms generated by FCM analysis revealed that only fresh leaves combined with LB01 buffer produced clean histograms with sharper peaks, reduced noise, and low coefficient of variation values. FCM analysis effectively classified the nodal explants of N. cadamba treated with colchicine into three distinct groups of polyploid plants: tetraploids, mixoploids, and octoploids. The N. cadamba tetraploids were found to have an estimated DNA content of 2.59 ± 0.09 pg, while octoploids showed an increase of DNA content to 5.35 ± 0.24 pg. These results highlight the effectiveness of FCM as a valuable tool in identifying mixoploids among the colchicine-induced polyploids of N. cadamba, as compared to the conventional method of chromosome counting. Mixoploids, which are characterized by cells with varying ploidy levels, deserve further investigation in future research.